2018
DOI: 10.1016/j.cortex.2018.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the microstructure of white matter in children and adolescents with Tourette syndrome measured using tract-based spatial statistics and probabilistic tractography

Abstract: Tourette syndrome (TS) is a neurodevelopmental disorder characterised by repetitive and intermittent motor and vocal tics. TS is thought to reflect fronto-striatal dysfunction and the aetiology of the disorder has been linked to widespread alterations in the functional and structural integrity of the brain. The aim of this study was to assess white matter (WM) abnormalities in a large sample of young patients with TS in comparison to a sample of matched typically developing control individuals (CS) using diffu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 87 publications
1
13
0
Order By: Relevance
“…The results demonstrated both marked and wide spread decreases in axial diffusivity together with altered white matter connectivity. The tic severity was associated with increased connectivity between primary motor cortex and the caudate nuclei [100]. These results provide putative evidence that altered connectivity of the insula might play a pivotal role in the pathogenesis of TS.…”
Section: Structural Connectivity Profilesmentioning
confidence: 55%
See 1 more Smart Citation
“…The results demonstrated both marked and wide spread decreases in axial diffusivity together with altered white matter connectivity. The tic severity was associated with increased connectivity between primary motor cortex and the caudate nuclei [100]. These results provide putative evidence that altered connectivity of the insula might play a pivotal role in the pathogenesis of TS.…”
Section: Structural Connectivity Profilesmentioning
confidence: 55%
“…Also, DTI studies have shown altered properties of white matter microstructure in cortico-striato-thalamocortical circuitry in patients with TS [98,99]. In another study, a large sample of young patients (age range, 8-21) were measured using tract-based spatial statistics and probabilistic tractography [100]. The results demonstrated both marked and wide spread decreases in axial diffusivity together with altered white matter connectivity.…”
Section: Structural Connectivity Profilesmentioning
confidence: 96%
“…Sigurdsson et al . examined white matter connectivity and water diffusivity in youth with TS, and report widespread decreases in axial diffusivity ( Sigurdsson et al ., 2018). The authors excluded subjects with high head motion, but even small head movements can affect DTI estimates ( Baum et al ., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Mutations in CLCN2 are responsible for leukoencephalopathy with ataxia ( 16 ). Several lines of evidence suggest that oligodendrocyte dysfunction and white matter disconnection are involved in the pathophysiology of GTS ( 17 , 18 ). Compared to healthy control, fractional anisotropy decreases and radial diffusivity increases in deep white matter tracts in cortico-striato-thalamo-cortical circuit as well as superficial white matter in GTS children; furthermore, lower fractional anisotropy values and higher radial diffusivity values in white matter regions are correlated with more severe tics (19).…”
Section: Discussionmentioning
confidence: 99%